Formation Mechanism of Ultra-High Temperature Nanocomposites by Mechanically Induced Self-Sustaining Reactions. Issue 11 (1st November 2016) - Nasiri-Tabrizi, Bahman; Ebrahimi-Kahrizsangi, Reza; Basirun, Wan Jefrey; Adhami, Touraj
Abstract : The mechanically induced self-sustaining reactions (MSRs) in TiO2 –B2 O3 –Mg–X (Al, C) quaternary system to synthesize various nanocomposite powders were investigated. Results showed that the phase compositions, structural features and morphological characteristics of the synthesized powders were notably influenced by the type and weight fraction of the reductants. Based on the morphological assessment, the mechanosynthesized nanocomposites had a unique flower-like cluster structure composed of loosely arranged nanosheets with a side length of about 400 nm and a thickness of about 25 nm.